Communication Strategy Of Police Investigators In Central Aceh Resort In Handling Children In Contact With Law - Achmad Surya; Viana Safrida Harahap; Hasiun Budi; Kaidah (LEGAL BRIEF, 2022)
Handling children in conflict with the law, finding various problems that hinder the interrogation process faced by investigators, namely those given by children are often convoluted, making it easier for investigators to collect evidence. The purpose of the study was to determine the communication strategy of the Central Aceh Resort Police investigators in dealing with children's cases, and to determine the factors that hindered the investigation strategy in children's cases. This research is a type of qualitative descriptive research, using a descriptive approach. Sources of data used are primary data and secondary data. The results of the study show that children's communication strategies in dealing with children's cases are carried out by persuasive communication techniques using clear, firm and straightforward language. Interpersonal communication techniques are also an option for investigators when interrogating children humanely by respecting human values. Factors that hinder investigators' communication strategies in dealing with children's cases, namely: First, the statements from children are always different, one of the most memorable events and answers to questions from investigators are often convoluted. Second, the child's lack of ability to understand the language used by the investigator during the interrogation process.